Challenges of developing and validating immunogenicity assays to support comparability studies for biosimilar drug development. (September 2012) - Cai, Xiao-Yan; Thomas, Jeff; Cullen, Constance; Gouty, Dominique
Imminent patent expiry for a number of biological products currently on the market (many of which are blockbusters) has created an increasing opportunity for the development of biosimilars in the biotechnology industry. The key for successful biosimilar development is to demonstrate biosimilarity to the originator drug. In addition to demonstrating the similarity of physical and chemical properties between biosimilar and originator compounds, regulatory agencies require that immunogenicity be evaluated in comparative studies between biosimilar and originator drugs. Immunogenicity assays are generally non-quantitative (qualitative) and proving similarity/comparability based on qualitative assays can be very challenging. This review will discuss the challenges of developing and validating immunogenicity assays to support preclinical and clinical comparative studies for biosimilar drug development as well as the challenges in association with the interpretation of the data.